Extensão rural, agroecologia e juventude rural: a experiência dos Agentes Promotores da Agroecologia (APAS), no Sertão do Araripe - Pernambuco - PIRES, Alexandre Henrique Bezerra (2011)
This research has as objective to analyze how the young people from rural areas of semi-arid lead in a different perspective of technical assistance and rural extension that uses the agroecology as a guiding of actions for sustainable development and what changes have occurred in attitudes and world view of these young. The research group participated in 2005, in a project supported by the National Technical Assistance and Rural Extension and developed by the Centro de Assistência e Apoio aos Trabalhadores e Instituições Não Governamentais Alternativas – CAATINGA, non-governmental organization that operates in Sertao do Araripe in Pernambuco. Through this project, young people participated in a training process with approaches that focus on the prospects of agroecology for the coexistence with the semiarid. These young developed activities in rural extension with the farming families in nine municipal districts during a year. It was firstly investigated how the organizations that are part of the Articulation in Semi-Arid in Pernambuco - ASA/Pernambuco to compose the framework in this research, among them the CAATINGA. They adopted the concepts about knowledge construction and local development, as well as what their methodological approaches close to family farmers in the semi-arid. It was also part of our investigation to identify which organizations developed specific work with young people and what strategies and approaches used by these organizations from the point of view of the construction of agroecological knowledge among the rural youth. The study sought to characterize the group of young APAs in terms of education, age, personal desires and personal experiences and in a familiar context. Another objective was to identify and analyze what were the learning and difficulties to join the group, the changes in attitudes, the involvement in community life and, finally, how they see each other before and after their participation in the group APAs. It was applied questionnaires with organizations and with young people for data collection questionnaires, and also, it was applied interviews with the Project coordinator and it was analyzed documents about. The survey results showed that in most organizations at ASA / Pernambuco develop actions in a perspective of coexistence, having the agroecology as the scientific approach. It was also evident in the adoption of some dimensions that comprise the local development, as the valorization of potential locations, the articulation with the several subjects and the systemic vision for a development in a sustainable basis. The results also show us that the action of rural extension in a perspective of the construction of agroecological knowledge among the rural youth produce significant impacts to the formation of a new generation of farmers, who have more clarity about their reality and more conditions to participate and to transform it. These conditions are given not only by the exercise of praxis, a fundamental principle of construction of knowledge, but also by facilities to the access to public policies, and also through the participation in community life, and mainly, to see how the subject of transformation can build a society more fair and sustainable.